IMPLEMENTASI SCADA UNTUK MONITORING DAN CONTROLING SERTA KOORDINASI SISTEM PROTEKSI GARDU INDUK SISTEM 1,5 BREAKER PADA GARDU INDUK TEGANGAN EKSTRA TINGGI BERBASIS ARDUINO MEGA 2560 DENGAN TAMPILAN HMI - Gumelar B, Muhammad Adi; Ariyanto, Eko (Vocational School Diponegoro University, 2017)
Muhammad Adi Gumelar B, Eko Ariyanto, SCADA is one tool that can monitor and control the system at the substation and can coordinate the protection system area when a disturbance occurs. SCADA monitors the device continuously. This paper is to understand Differential protection areas, CCP, Buspro, and CBF that work when there is interference, namely internal and external interference by applying SCADA as its coordination. 12V DC relay is used as PMT, ACS712 as CT, and Ethernet Shield as Modbus to connect Arduino Mega 2560 with SCADA. Arduino Mega 2560 functions as a controlling center of input and output. The input used is the ACS712 sensor as a detector of the current flowing in the circuit. The Arduino Mega 2560 output signal will be sent to SCADA using an Ethernet Shield and router. Status of substations 1.5 breakers can be monitored with HMI from anywhere by using the SCADA application. In the event of a disturbance, each ACS712 will start reading the current changes and will be processed by Arduino Mega 2560, so that it can determine the protection area that works and trip the relay, SCADA will automatically record disturbances and give an alarm to occur by turning on the protection LED and sounding buzzer alarm.